CHARACTERISTICS OF THE EFFECT OF STORAGE CONDITIONS ON THE QUANTITATIVE CONCENTRATION OF NITRATES IN FOOD PRODUCTS - Прилипко, Татьяна; Коваль, Т.В.; Косташ, В.Б. (SWorldJournal, 2024)
The results of the study of sources of nitrosamines entering food products are presented. HAs have been detected in various types of fish and fish products, and less HAs are found in fresh fish. It was established that the technological processing of fis